2021
DOI: 10.1029/2020jd033821
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Effects of Surface Energy Partitioning on Convective Organization: Case Study and Observations in the US Southern Great Plains

Abstract: Evapotranspiration not only directly provides water vapor for precipitation, it also influences convective precipitation by changing atmospheric dynamics and stability (Schär et al., 1999). The interaction of convection with the land surface is complicated because it depends on the lifecycle stage of convective precipitation-isolated convective cells are initially triggered, but can grow upscale into organized clusters. Atmospheric state-dependence, spatial heterogeneities in soil and vegetation, and spatial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Dai et al. (2021) and Grant et al. (2018) found that even with weakened cold pools, the convection can be enhanced in their simulations because of more upright updrafts between the cold pool and the environment in later stages, or due to less entrainment of cold pool air into updrafts.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Dai et al. (2021) and Grant et al. (2018) found that even with weakened cold pools, the convection can be enhanced in their simulations because of more upright updrafts between the cold pool and the environment in later stages, or due to less entrainment of cold pool air into updrafts.…”
Section: Introductionmentioning
confidence: 96%
“…The interaction of cold pool with environmental conditions affects the evolution of convection (e.g., James et al., 2005; Rotunno et al., 1988; Weisman & Rotunno, 2004). The roles of cold pool depend on the convective lifecycle stage, and vary under different surface conditions (e.g., Dai et al., 2021). Dai et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dai et al. (2021) describe that regions with higher LH flux could preferentially trigger convection by lowering the level of free convection (LFC) closer to the top of the PBL. While both the Noah and Noah‐MP experiments contain high LH values, the increased SH in Noah‐MP will aid in providing the buoyancy needed to reach the LFC and, therefore, the Noah‐MP LSM would be more likely to trigger and sustain deep convection.…”
Section: Resultsmentioning
confidence: 99%